The relationship of crime to society in the countries of Asia and the Arabs - MOHAMMED HAMD MOHAMMED ALEHIRIRSH (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The study’s overarching goal is to review and advance Libyan criminal law by uncovering and analyzing domestic violence and studying it in depth, openly, and independently. Compare and contrast international social science research. So that Islamic law will be treated equally. The study also seeks to keep an eye on the legal system and to determine what the law is by comparing the legal sanction set by Libyan legislators with Islamic law.Method: Using a descriptive analysis strategy, the researcher compiles information from textbooks and encyclopedias on Libyan criminal law. Information about Islamic law comes from a variety of books called fiqh. The researcher then organizes the information by topic and reviews it using the lens of Libyan law and the opinions of four prominent ulemas. The final steps of any scientific process involve making comparisons and drawing conclusions.Findings: The outcome demonstrates that the Libyan lawmaker has followed Islamic principles in legitimizing domestic violence. In some instances, however, the law must be applied in a way that diverges from its usual form to protect human rights, public safety, and social stability. The inability of the law to evolve and adapt to changing circumstances is the root cause of the situation. Domestic violence and improper use of a mediator are left to the jurisdiction of criminal law, which is why they are not addressed directly in Libyan family law. The clarification of the family condition in criminal law, however, will help to strengthen the argument.Implications/Novel Contribution: Due to the relevance of the topic, the researcher hopes to attract the attention of those in charge at judicial bodies, human rights organizations, and scientific institutions so that they can receive a comprehensive study of these crimes, complete with analysis, description, development, and treatment of deficiencies, as well as codification of new standards, all of which are in strict accordance with Islamic law.